TRANSVERSALIDADE, MEIO AMBIENTE E SUSTENTABILIDADE NA FORMAÇÃO DO EDUCANDO - Maneia, Arismar; Krohling, Aloisio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611705641 The environmental crisis generated by the accelerated development of industries and of runawaypopulation growth on the planet has been aggravated and purchased large, including pollution. Thus,the goal of this work is to show that environmental education, understood as essential task to humanlife, should be practiced in schools and organizations to change the current frame. In addition,evidence that the socialization of actions, both internal and external, geared to the fulfillment ofsocial and environmental responsibility also has as main feature the participation of all the subjectsinvolved in the organizational processes of Higher Education Institutions – HEI, which requires thepreparation of environmental management strategies that prioritize the implementation ofenvironmental initiatives in the context of environmental education programs. Bibliographicalresearch was exploratory qualitative and descriptive type, in order to provide the direct contact of the researcher with the work that deals with the topic under study. The study concluded that socialresponsibility is part of a new conception of society which could not get beyond the HEI and that thesearch for solutions to environmental problems is not a commitment that the HEI should or shouldnot meet, but that it is an obligation, which, if not met, makes a socially irresponsible.